A teoria da complexidade na aprendizagem de espanhol em Teletandem - Oyama, Andressa Carvalho Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Language learning is admittedly a complex phenomenon. However, approaching it from the perspective of complexity theory is an activity only recently applied in linguistics. Thus, seeking to fill another gap in the area of Applied Linguistics, this study examines the development of the interlanguage of brazilian learners of spanish in context Teletandem under the view of the Complexity Theory. The use of this theory allows to see, in this scenario, the presence of fruitful dynamics, randomness, nonlinearity, emergence of new standards, bifurcations, control parameters and attractors. It is adopted an analysis mostly qualitative, using virtual interactions between peers that, while learning a foreign language, encourage the learning of their partner in portuguese. With data from sessions – in chat, audio and chat, and audio only – of four pairs of students, combined with data from questionnaires, interviews, and daily about mediation sessions, it was possible to realize that Teletandem complex context is not only the interactional environment, but rather has an active performance in learning, changing and being changed by the agents and elements presents. It is a macro system in which the interlanguage development occurs, that is characterized as a complex subsystem insert in each complex system that is the inter(agents). It was possible to identify, in the interlinguistic development, characteristics of a strange attractor. However, as it is observed cognate languages, by the dynamic and recurring blend of portuguese and spanish, is the generated a system that oscillates between cyclical and random, leading to a topography of an almost ‘plain’ in the valley of foreign language learning

A aprendizagem de línguas é reconhecidamente um fenômeno complexo. No entanto, abordála a partir da perspectiva da Teoria da Complexidade é uma atividade só recentemente aplicada em linguística. Assim, buscando preencher mais uma lacuna na área de Linguística Aplicada, este estudo analisa o desenvolvimento da Interlíngua de brasileiros aprendizes de espanhol em contexto Teletandem à luz da Teoria da Complexidade. O uso dessa teoria permite vislumbrar, nesse cenário, a presença de profícua dinamicidade, aleatoriedade, não linearidade, emergência de novos padrões, bifurcações, parâmetros de controle e atratores. Adota-se uma análise majoritariamente qualitativa, com uso de interações virtuais entre pares que, ao mesmo tempo em que aprendem uma língua estrangeira, fomentam a aprendizagem de seu parceiro em relação à língua portuguesa. Com dados de sessões – em chat, áudio e chat e somente áudio – de quatro pares de interagentes, conjugados a dados de questionários, entrevistas, sessões de mediação e diários, foi possível vislumbrar que o contexto complexo Teletandem não é somente o ambiente interacional; antes, mostra-se como atuante na aprendizagem, modificando e sendo modificado pelos agentes e elementos presentes. Trata-se de um sistema macro, no qual ocorre o desenvolvimento da Interlíngua, que se caracteriza como um subsistema complexo inserto no sistema complexo que é cada (inter)agente. Foi possível identificar, no desenvolvimento interlinguístico, características de um atrator estranho. No entanto, como se trata de línguas próximas, pela própria dinâmica recorrente de mescla entre português e espanhol, há a geração de um sistema que oscila entre o cíclico e o aleatório, levando a uma topografia de quase ‘planície’ no vale da aprendizagem de língua estrangeira
Keywords: Ensino à distância; Lingua espanhola - Estudo e ensino; Interlingua (Aprendizagem de linguas); Distance education